Pendampingan Strategi Bisnis dan Digitalisasi Pemasaran untuk UMKM Optik Best Vision Solution - Retnowati, Ayu Nike; Pratiwi, Sintia Putri; Azhar, Arfah Nurlaela (Ma'soem University, 2025)
Eye health is a crucial in improving the quality of life, especially in the digital era. Best Vision Solution (BVS) Optik, a micro-enterprise located in Banjaran, Bandung Regency, aims to address this need through eye examination services and the sale of eyeglasses. However, BVS Optik faces internal challenges such as limited digital promotion, minimal capital, and a shortage of personnel. On the other hand, significant opportunities exist, including the trend of glasses as fashion accessories and the lack of digital marketing among competitors. This community engagement project aims to conduct a comprehensive strategic analysis of BVS Optik's internal and external conditions to formulate appropriate and sustainable business strategies. The analysis was carried out using SWOT, IFAS, EFAS, and strategic mapping tools such as the BCG Matrix, GE Matrix, and TOWS Matrix. The results indicate that BVS Optik operates in an industry with high market attractiveness, although its internal capabilities remain moderate. Based on these findings, several strategies are recommended, including optimizing digital promotion, enhancing product visual appeal on social media, offering service bundling packages, leveraging marketplace platforms, providing online eye consultations, and conducting regular eye check-up programs. These strategies are expected to enhance BVS Optik’s competitiveness and significantly expand its market reach.